Determining the standardized ileal digestible lysine requirement of 6.8 to 15.9 kg pigs - Vier, C. M.; De Souza, I. B.; De Jong, J. A.; Goncalves, M. A. D.; Jones, A. M.; Goodband, Robert D.; Tokach, Michael D.; DeRouchey, Joel M.; Woodworth, Jason C.; Dritz, Steven S. (My University, 2016)
A total of 300 maternal line barrows (DNA; 200 × 400, initially 6.75 ± 0.23 kg BW) were used in a 21d trial to determine the standardized ileal digestible (SID) Lys requirement of nursery pigs from 6.8 to 15.9 kg. Pigs were randomly allotted to pens at weaning based on BW and were fed a common diet for 9 d after weaning. There were 10 replicate pens/treatment and 5 pigs/pen. Pens of pigs were allotted to experimental diets based on average BW, in a completely randomized design. The 6 dietary treatments consisted of 1.05, 1.15, 1.25, 1.35, 1.45, and 1.55% SID Lys and were achieved by increasing the inclusion of crystalline amino acids, allowing soybean-meal to stay constant across dietary treatments. Experimental data was analyzed using general linear and nonlinear mixed models with heterogeneous residual variances and pen as the experimental unit. Competing models included linear (LM), quadratic polynomial (QP), broken-line linear (BLL), and broken-line quadratic (BLQ). The best-fitting model for each response was selected using Bayesian information criterion (BIC). Increasing SID Lys linearly improved (P = 0.001) G:F. There was a marginal quadratic response for ADG (P = 0.067) with increasing SID Lys. The ADFI increased in a quadratic manner (P = 0.019) from 1.05 to 1.25% SID Lys. For ADG, the best-fitting comparable models were BLL [predicted equation: 462– 271 × (1.29– Lys), if SID Lys < 1.29%] and BLQ [predicted equation: 465– 372 × (1.47– Lys)2, if SID Lys < 1.47%], estimating the requirement at 1.29% (95% CI: [1.23, 1.35]%) and 1.47% (95% CI: [1.31, > 1.55]%), respectively. For G:F, the best-fitting models were QP [predicted equation: 0.750– 0.317 × (Lys) + 0.214 × (Lys)2] and LM [predicted equation: 0.392 + 0.241 × (Lys)], estimating the requirement at greater than 1.55% for both models. In conclusion, the estimated mean SID Lys required for nursery pigs from 6.8 to 15.9 kg ranged from 1.29% for maximum ADG to at least 1.55% for maximum G:F.
Citation: Vier, C. M., De Souza, I. B., De Jong, J. A., Goncalves, M. A. D., Jones, A. M., Goodband, R. D., . . . Dritz, S. S. (2016). Determining the standardized ileal digestible lysine requirement of 6.8 to 15.9 kg pigs. Journal of Animal Science, 94, 191-191. doi:10.2527/msasas2016-408
Keywords: Growth; Lysine; Nursery Pig; Agriculture